Exploring Parents' Motivations for Sharenting and Consequences for Children's Well-Being - Motevalli, Saeid; Razak, Rogayah A.; Bailey, Richard Peter; Madihie, Amalia; Mehdinezhadnouri, Katayoun; Pan, Yifei (International Journal of Child Health and Nutrition, 2025)
Introduction: This literature review uses thematic analysis to identify common themes and topics in recent literature on the perceptions, attitudes, and motivations towards parents’ sharenting behavior. Objective: This study investigates perspectives on sharenting—the practice of parents posting content about their children on social media—and the rationale behind this behavior. As digital platforms become more integrated into family life, understanding the motives for sharing is critical for assessing their social, ethical, and developmental consequences. Methods: Articles were selected through a literature search. We eliminated articles that included sharenting, sharenting practices in Malaysia, impression management and sharenting, and reinforcement theory and sharenting. 41 articles were chosen and reviewed to identify the main topics of discussion. Findings: This study identifies major motives for sharing, as revealed through qualitative interviews and surveys with parents and social media users, including a need for social connection, community support, and documenting parenting milestones. The findings reflect a variety of viewpoints on the practice, with some seeing sharing as a way to celebrate parenting and develop relationships. In contrast, others are concerned about privacy and the digital legacy left for children. Conclusion: By analyzing these perspectives, the study contributes to the broader discussion of digital parenting practices and sheds light on the balance between sharing and privacy in the digital era. This study emphasizes the importance of raising parental awareness and providing help as they navigate the difficulties of social media sharing. Recommendation: These results serve as a reference for future child psychology and mental health research. Thus, it is recommended that parental sharenting behavior be further explored, and a suitable legal framework should be established in Malaysia to govern and manage this issue before violations related to sharenting, such as digital kidnapping and cyberbullying, become difficult to address in the Malaysian context.